Fighting spam with reputation systems. - Prakash, Vipud Ved; O'Donnel, Adam. (New York ACM, 2005)
Spam is everywhere, clogging the inboxes of e-mail users worldwide. Not only is it an annoyance, it erodes the productivity gains afforded by the advent of information technology. Workers plowing through hours of legitimate e-mail every day also must contend with removing a significant amount of illegitimate e-mail. Automated spam filters have dramatically reduced the amount of spam seen by the end users who employ them, but the amount of training required rivals the amount of time needed simply to delete the spam without the assistance of a filter.Considering that spam essentially consists of a single unwanted message seen by a large number of individuals, there is no reason why the training load associated with an automated spam filter can't be distributed across that community of individuals. The community comes together and jointly classifies new messages as spam or not spam, and then allows those decisions to be distributed to the community.The collaborative decision-making of the community reduces not only the training cost for an individual in the community, but also the accuracy cost, or the cost associated with misclassification of a message, be it spam classified as not spam or vice versa. If the community is able to reduce the false-positive rate through properly training a spam filter, then the costs incurred to the sender of a legitimate message misclassified as spam, as well as the costs incurred to a receiver who wants to read said misclassified message, are reduced.The reduction of training and accuracy costs is the primary motivation behind the creation of collaborative spam filtering architectures. These systems allow users to submit fingerprints of spam messages that, when approved by the community of users, are then placed in a catalog of known spam messages.
Keywords: Information Systems; Information Systems Applications; Communications Applications; Electronic Mail; Computing Milieux; Management of computing and information systems; Project and People Management; System management; Security and Protection; Economics; Human factors; Theory